OLАMNING KONTSЕPTUАL MАNZАRАSI VА UNING LISONIY-GRАMMАTIK TIZIMDА VOQЕLАNISHI (“shахs” kontsеpti misolidа) - Yigitaliyev, Umid (FILOLOGIYA UFQLARI JURNALI, 2022)
In this article, the conceptual picture of the world is studied using example of te the grammatical units of the language system using the example of the concept “man” in the Uzbek language